Global Scaling Up Sanitation Project : Global Learning Strategy - Frischmuth, Christiane (World Bank, Washington, DC, 2017)
The purpose of this learning strategy is to develop a structured process of generating, sharing, capturing, and disseminating knowledge about what works in scaling up and sustaining sanitation programs. The authors are undertaking this learning process in order to enable evidence-based decisions by policy-makers and implementation of large-scale programs. The learning in this project will benefit not only current stakeholders but also future stakeholders interested in and committed to promoting and implementing effective large-scale sanitation programs. The remainder of this strategy paper is divided into five sections: project background; learning goals and principles; learning culture, tools, and platforms; learning process; and organizational aspects of learning.